DAMPAK PERUBAHAN SISTEM PEMERINTAHAN DESA TERHADAP KINERJA PENGELOLAAN DAN PEMANFAATAN SUMBERDAYA PERIKANAN DI PEDESAAN MALUKU - Venda Jolanda Pical; John Haluan; M. Fedi A. Sondita; Victor P.H. Nikijuluw (Buletin PSP, 2007)
Several policies of central government through the regulations of regional government have a big effect so far on the changes of the community institution structure in the villages, especially the system of village government that have an impact on the management and the exploitation of the fishery resources in Moluccas villages. The aim of research are : to evaluate the performance of the fishery management system in Moluccas villages and to compare the performance of the fishery management system between sasi villages, the village practices the tradition of fishery community-base management, and non sasi village. It is hope that the research would be functioning as an information source for regional government in organizing and planning of sustainable fishery management in Moluccas villages. The results of research showed that the changes of the village government system had an effect on the performance of fishery resources management in Moluccas villages. The performance of fishery resources management was not different between the sasi village and non sasi village. It is recommended that there should be an effort to make the community-base management of fishery resources existed effective. There should be an effort to increase co-management.